PATH COEFFICIENT ANALYSIS OF TOTAL SOLUBLE SOLIDS IN SOLANUM LYCOPERSICUM L. - Shokat, S.; Azhar, F. M.; Zia, M. B. (The Nucleus, 2011)
Genetic correlation coefficients were partitioned using path coefficient analysis to examine direct and indirect effects of plant characters on total soluble solids (TSS) in Solanum lycoprsicum (L.). Analysis of variance for number of days to 50% flowering (NDFL), number of days to 50% fruit setting (NDFR), number of flowers per cluster (NFLC), number of fruits per cluster (NFRC), fruit length (FRL), fruit width (FRW), fruit firmness at pink stage (FFP), fruit firmness at red stage (FFR), pericarp thickness (PT), pH of the juice (pH) and TSS revealed significant genotypic differences for all the characters. Results showed that genotypic correlation of NFRC and NDFL with TSS was positive and significant. Path coefficient analysis showed that NFRC had contributed directly to TSS followed by FRL, FFR and FRW and may be given due consideration.